Initial Psychological Response of Various Population Groups to COVID-19 Pandemic: A Cross Sectional Study - Shahzaib Ahmad; Ahmed, Shahzaib; Muhammad Abubakar Shahid Chishti; Usman Hotiana; Tania A. Shakoori (Proceedings, 2021)
Introduction: The corona virus pandemic has brought with it psychological problems like anxiety, stress, and depression. Research studies are urgently required to generate data that would help formulate strategies to manage the ensuing psychiatric and psychological maladies at societal level. Aims & Objectives: The aim of our study is to better comprehend the initial psychological response of society to COVID-19 outbreak though a survey. Place and duration of study: This cross-sectional study was conducted in King Edward Medical University, Lahore from April 2020 to October 2020. Material & Methods: An online questionnaire comprising of 20 items including the Zung self-rating Anxiety Scale (SAS) was disseminated to three fifty (350) participants. Two hundred and seventy-one (n=271) responses were received. Collected data was entered and analyzed using the SPSS software version 20. Categorical variables were presented as frequencies and percentages. Relationships between categorical variables were tested by Chi square test. Regression analysis was conducted to investigate the effect of various variables on total stress score. A p-value of <0.05 was considered significant. Results: It was revealed that 85.2% of the respondents reported minimal psychological impact, 14.8% had mild to moderate anxiety levels and 0.4% reported marked to severe anxiety. The impact was 2.5 times greater in subjects belonging to lower socioeconomic status (p=0.02). Conclusion: Population belonging to lower socioeconomic class is more vulnerable to be impacted by psychological disturbances due to the pandemic owing to economic losses that are magnified in the population with fragile earning sources.